INTEGRASI METODE SWOT DAN AHP DALAM STRATEGI PENGEMBANGAN PETERNAKAN SAPI RAKYAT DI KABUPATEN TIMOR TENGAH UTARA - Taus, Igniosa (Fakultas Pertanian, Universitas Janabadra, 2024)
Cattle farming businesses need to be developed to support the food security program launched by the Indonesian government. North East Timor Regency (TTU) This research aims to design several strategies for developing cattle farming in TTU Regency. Data collection was carried out by interviews with seven respondents and observations. Secondary data was collected from the Central Statistics Agency (BPS) and the Livestock Service, as well as documentation as supporting data. The results of this research are that the Head of the Livestock Service is an actor who plays a very important role in the sustainability of people's cattle farming. Internal factors obtained a total score of 3.25 and external factors obtained a total score of 2.70. Cattle farming in TTU Regency is in quadrant four, which means its position is growing and developing. The priority strategy for developing cattle farming is the integration strategy with the first highest choice, namely integration strategy 2, adding UPTD and cooperatives at every point in the potential area, the second highest strategy, namely integration strategy 4, providing periodic cattle cultivation technology training and the third highest strategy, namely integration strategy 1, providing efforts village level assistance officers.